Is Extended Trochanteric Osteotomy Safe for Use in Two-stage Revision of Periprosthetic Hip Infection? A Systematic Review - Malahias, Michael-Alexander; De Filippis, Roberto; Kostretzis, Lazaros; Gu, Alex; De Martino, Ivan; Sculco, Peter K. (The Journal of Hip Surgery, 2020)
Several clinical trials have retrospectively evaluated the role of extended trochanteric osteotomy in two-stage total hip arthroplasty (THA) revision for the management of periprosthetic joint infection of the hip. However, no systematic review of the literature has been published to date to evaluate the clinical, functional, and radiographic outcomes of extended trochanteric osteotomy (ETOs) performed as part of implant removal during a two-stage revision for the management of periprosthetic joint infection (PJI). The US National Library of Medicine (PubMed/MEDLINE), and the Cochrane Database of Systematic Reviews were queried for publications from January 1980 to April 2019 using the following keywords: “extended” AND “trochanteric” AND “osteotomy.” Six studies included in this systematic review assessed 305 cases (281 patients) of PJI treated surgically with two-stage revision combined with ETO at the first stage. The mean overall union rate of the ETO was 97%, while the overall rate of radiographic femoral stem subsidence >5 mm was 5%. In addition, the overall mean infection-free rate of two-stage revision combined with ETO was 94% (288 out of 305 operated hips), while the overall complication rate requiring reoperation was 8% (26 out of 305 operated hips). Finally, there was some evidence to show that two-stage revision with ETO was associated with improved infection-free rates compared with two-stage revision without ETO. ETO seems safe and effective in patients with well-fixed femoral stems who require two-stage THA revision for the management of chronic PJI. Two-stage revision with ETO might result in improved infection-free rates compared with two-stage revision without ETO.
Keywords: extended trochanteric osteotomy; periprosthetic joint infection; two-stage revision; total hip arthroplasty; femoral stem subsidence; systematic review